Second Handbook of Information Technology in Primary and Secondary Education (Springer International Handbooks of Education,, 2018)
In this second edition the editors continue their efforts to synthesize research and practice and project future directions in the field of information and communication technology. The proliferation of mobile devices and applications have had major implications on how the nature of teaching and learning should be conceptualised, and what pedagogical practices should be used to support bridging formal and informal learning. The advent of social media also highlights the importance of gaining a deeper understanding of social learning theories and computer-supported collaborative learning theories and practices. The advancement of new technologies to support easy accessibility of educational resources such as OER and to a lesser extent MOOCs have led to the debate on how assessment should be conducted and how technologies could be used to support it. The demand of the knowledge society requires that researchers, policy makers, and educational practitioners be conversant with new research findings in order to understand the impact of ICT in teaching and learning, and how to support learners to use new technologies and applications creatively and effectively. New research paradigms have emerged to meet these challenges. .